Higher Education and New Target Groups - Vasconcelos, Rosa (2012)
The implementation of the Bologna Process in the Portuguese Higher Education system led to deep changes at this educational level. In order to harmonize and to level the Portuguese higher education with other European countries several measures were determined, including access expansion, especially for new target groups. Among others the +23 year old students and Technology Specialization Courses (CET) are considered new target groups. In order to understand the evolution of new public courses in Engineering and Technology at University of Minho, a study of students who entered through the quotas of the academic years 2005/2006 to 2010/2011 was carried out in order to analyze the academic path. Understanding their journey in higher education can help to improve the system of teaching and learning of this new audience. This paper compares those two groups’ performance in order to understand the difference between them and the ordinary students.